Analysis of The Design of Coconut Sleep Machine Operator Chair Development With Ergonomic Principles To Reduce The Risk of MSDS Musculosceletal Disorders in Kelapa Tiga Putra - Muhammad Fahmi Adityah; Akhmad Wasiur Rizqi; Yanuar Pandu Negoro (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The production process in SME KelapaTiga Putra still uses human labor as well as the milling process which has not applied ergonomic principles. If the work posture is in a position that is less ergonomic, it can cause complaints in parts of the body such as the back, waist, neck, arms and it can lead to musculoskeletal risk. By paying attention to the situation at work, a tool will be made that if it can change a less ergonomic position into an ergonomic one. The design of this tool aims to simplify the coconut milling process using the anthropometric method. The object of this research focuses on the coconut milling process workers. There are three methods used, namely the NBM questionnaire to find out complaints, analysis of work postures using the REBA method, anthropometry used as a measure of aid. The results of the NBM questionnaire have complaints with a score of 65 with a very high level of risk. Classification of the level of risk of the musculoskeletal system based on the total score of individual workers having complaints with a score of 65 with a very high level of risk means that coconut mill workers need comprehensive action as soon as possible. Analysis of the initial work posture has a very high risk, while the analysis of the final work posture after using the tool has a very low risk. The anthropometric percentile used is the 50th percentile with the size of the tool. Chair back height 54.89 cm, chair back width 38.75 cm, seat seat width 32.32 cm, chair leg height 40.07 cm, seat seat length 39.88 cm